Effect of operating conditions in removal of arsenic from water by nanofiltration membrane - Saitua, Hugo Alberto (2005)
The removal of arsenic from synthetic waters and surface water by nanofiltration (NF) membrane was investigated. In synthetic solutions, arsenic rejection experiments included variation of arsenic retentate concentration, transmembrane pressure, crossflow velocity and temperature. Arsenic rejection increased with arsenic retentate concentration. Arsenic was removed 93-99% from synthetic feed waters containing between 100 and 382 gg/L As V, resulting in permeate arsenic concentrations of about 5 gg/L. Under studied conditions, arsenic rejection was independent of transmembrane pressure, crossflow velocity and temperature. In surface water, the mean rejection of As V was 95% while the rejection of sulfate was 97%. The co-occurrence of dissolved inorganics does not significantly influence arsenic rejection. The mean concentration of As in collected permeated was 8 pg/L. The mean rejection of TDS, total hardness and conductivity were 75, 88 and 75% respectively.